(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This study explores the effectiveness of self-assessment and peer assessment techniques in enhancing the writing skills of language learners. These approaches promote learner autonomy, critical thinking, and constructive feedback, which are crucial for improving writing accuracy and fluency. The research employs a mixed-methods approach, combining quantitative analysis of writing performance before and after intervention with qualitative data from learner feedback and reflections. The results indicate that incorporating self and peer assessment in the language classroom significantly improves writing quality, learner motivation, and awareness of linguistic features. The study also discusses challenges and recommendations for effective implementation of these assessment strategies. Moreover, the study highlights the importance of training both teachers and learners to effectively implement these assessment methods, ensuring a supportive environment that encourages honest and constructive feedback. This approach not only improves writing skills but also prepares learners for lifelong autonomous learning